In silico Analysis of 6, 6’-Dihydroxythiobinupharidine on the Enzymes Involved in Cognitive Impairment - Nayak, Pranav; Ali, Mohammad; Bharathi, DR (International Journal of Pharmaceutical Investigation, 2026)
Background Cognitive impairment signifies a reduction in mental abilities resulting from different factors like Alzheimer's disease leading to a diminished quality of life. Detecting it early and implementing interventions can assist in symptom management. This research aimed to explore the interactions between 6,6’-Dihydroxythiobinupharidine (DTBN) and the various enzymes involved in cognitive impairment. Materials and Methods We downloaded protein molecules from the protein data bank and DTBN from the PubChem database. The proteins were docked with DTBN using AutoDock software to analyze their interactions. The Schrödinger suite was used to assess the flexibility of the docked DTBN. Results and Discussion Interaction of DTBN with AChE, BuChE, BACE1, GSK-3β, MAO-B, and MAO-A showed a docking score of >˗9kcal/mol. Among these, MAO-B showed a good score of ˗10 kcal/mol after binding to the active site residue Pro102. However, molecular dynamic simulation showed that DTBN did not form a stable and rigid complex with any of these proteins. Conclusion Although DTBN showed a good docking score, it failed to form stable and rigid complexes. Thus, DTBN is not effective against the enzymes involved in cognitive impairment.
Keywords: 6,6’-Dihydroxythiobinupharidine; Acetylcholinesterase; Alzheimer’s disease; Butyrylcholinesterase; Cognitive impairment; Docking.